Investigation the Residues of Lanit and Confideur in Some Vegetables in Local Markets in Wadi Al Shati Area - AYA . A . Ehmeid , M. A. Elssaidi (Journal of Pure & Applied Sciences, 2019)
This study examines the residues of lanite and confidir pesticides in the local markets in the southern region on some vegetables in the market (tomatoes, boiling, garlic) and the application of some health risk assessment criteria (daily consumption rate of pesticide DIR, health risk index HRI) to consumers In the southern regions (Shati, Sabha, Murzuq, Ghat, Al-Qatrun) in addition to evaluating some quality characteristics of pesticides. The results showed that the pesticide label did not meet the typical label specifications and the concentrations of the active substance of the pesticides were below the percentage indicated on the label (83%, 16.38% for Annette and Confidore respectively, instead of 90%, 20%). The results of the health risk index of lanite pesticide showed that it exceeded the risk (1) in tomatoes in all southern regions except Murzuq and the highest index in the beach (1.499), ... The health risk indicator for CONFIDOR did not exceed the index in all vegetables and regions. The average daily consumption of lanite was the highest consumption of tomatoes and the lowest consumption of garlic in all regions, while the average daily consumption of CONFIDER was the highest consumption of tomatoes and the lowest consumption of garlic in all regions. The concentrations of lanite residues in the studied vegetables exceeded the permissible limits except for garlic and the highest concentration was in tomatoes (15.62 (15.62 µg / g), while the concentrations of confederate residues did not exceed the permissible limits.